Experimental signatures of electron cyclotron wave energy condensation in magnetic islands. (22nd September 2021) - Bardóczi, L.; Logan, N.C.
Abstract: Bifurcation of the electron temperature perturbation (Δ T e ) in magnetic islands due to electron cyclotron current drive (ECCD) is reported for the first time in toroidal plasmas. In this DIII-D experiment Δ T e spontaneously increases by 50% in a growing 2, 1 island which in turn rapidly shrinks, consistent with improved stabilization by the ECCD due to the temperature bifurcation. This non-linearity of Δ T e maps out a hysteresis in the island evolution cycle, in qualitative agreement with the theoretically predicted radio frequency current condensation effect Reiman and Fisch 2018 ( Phys. Rev. Lett. 121 225001). Therefore, this observed bifurcation can be critical for the avoidance of disruptions caused by tearing modes in tokamaks.